Genome Sequencing Reveals the Complex Polysaccharide-Degrading Ability of Novel Deep-Sea Bacterium Flammeovirga pacifica WPAGA1 - Gao, Boliang; Jin, Min; Li, Li; Qu, Wu; Zeng, Runying (Frontiers in Microbiology, 2017)
Flammeovirga pacifica strain WPAGA1 is a Gram-negative, polysaccharide-degrading bacterium isolated from the marine sediment of the West Pacific Ocean. This strain is a cosmopolitan marine bacterium that uses complex polysaccharides as exclusive source of carbon and energy and plays a key role in the marine carbon cycle. Genome sequence analysis of strain WPAGA1 revealed that the assembled fine genome contains 6,610,326 bp with 32.89% G+C content, 5036 open reading frames (ORFs) and abundant genomic elements. Amongst these ORFs, 1022 genes encoding carbohydrate enzymes were found in the F. pacifica WPAGA1 genome. In addition, abundant putative enzymes involved in degrading polysaccharide were found. These enzymes include amylase, xylosidase, cellulase, alginate lyase, pectate lyase, rhamnogalacturonan lyase, chitinase, carrageenase, heparinase and fucosidase. To further investigate the use of these polysaccharides in strain WPAGA1, a schematic of various polysaccharide-degrading metabolic pathways were deduced from the genome sequence. This study showed that strain WPAGA1 may serve as a potential candidate for research of glycometabolism and have potential biotechnological and industrial applications and play key roles in the marine carbon cycle.